Rector's control and features of its conduct in the conditions of distance learning - Nikulina, N.; Zavgorodnii, I.; Pertsev, D.; Krasnikova, S.; Marakushyn, D.; Bahlaienko, T. (New Collegium, 2021)
The work is devoted to the importance of the rector's control as a means of internal monitoring in the management system of the quality of education in higher education institutions. The scientific and pedagogical community perceives the monitoring procedure and its essence as a dynamic tool with constant updating and feedback, through which it is possible to control and manage the quality of education, considerable attention is paid to the study of levels, conditions and means of monitoring, as well as its functionality. Scientific research conducted on the basis of higher medical educational institutions is a very important contribution to the study of this issue. The value of such studies is due to the fact that they focus on the quality of professional training of future doctors, which is related to international standards and requirements for specialists in this field. Taking into account the importance of quality education in the medical field, a format of the rector's control as a monitoring tool has been developed on the basis of Kharkiv National Medical University. Such control allows to assess the contribution of both students and teachers in the educational process, to prepare for medical licensing exams, to check the level of knowledge acquisition of practical skills and techniques for providing emergency medical care, as well as for training sessions. The rector's control covers domestic and foreign third- and final-year students, because this contingent is preparing for licensing exams, as well as all contingents of 5th-year students as part of testing the level of practical skills. This means of monitoring fully justifies itself, the method is convenient and mobile, it is always possible to identify the effectiveness of the university departments, as well as students whose level of knowledge does not meet the requirements. However, due to the global COVID-19 pandemic and quarantine measures on the territory of Ukraine, the university switched to distance learning in order to prevent the spread of the disease. Thanks to modern technologies that provide distance learning, the university has managed not to stop curricula. But when it comes to testing the students’ level of knowledge, the atmosphere in the distance format is lost as when passing medical licensing exams, and one of the key concepts such as "CONTROL" is excluded, it remains only to rely on the students’ responsibility. It is impossible to check the acquisition of practical skills and methods of providing emergency medical care, because in addition to the theoretical part, there is a demonstration of skills on simulators of different levels of complexity in its format.